Comparing Two Automated Techniques for the Primary Screening-Out of Urine Culture - Millán-Lou, María Isabel; García-Lechuz, Juan Manuel; Ruiz-Andrés, María Angeles; López, Concepción; Aldea, María José; Egido, P.; Revillo, María José; Rezusta, Antonio (Frontiers in Medicine, 2018)
Urinary tract infection is the most common human infection with a high morbidity. In primary care and hospital services, conventional urine culture is a key part of infection diagnosis but results take at least 24 hours. Therefore, a rapid and reliable screening method is still needed to discard negative samples as quickly as possible and to reduce the laboratory workload. In this aspect, this study aims to compare the diagnostic performance between Sysmex UF-1000i and FUS200 systems in comparison to urine culture as the gold standard. From March to June 2016, 1,220 urine samples collected at the clinical microbiology laboratory of the “Miguel Servet” hospital were studied in parallel with both analysers, and some technical features were evaluated to select the ideal equipment. The most balanced cut-off values taking into account bacteria or leukocyte counts were 138 bacteria/µL or 119.8 leukocyte/µL for the UF-1000i (95.3% SE and 70.4% SP), and 5.7 bacteria/µL or 4.3 leukocyte/µL for the FUS200 (95.8% SE and 44.4% SP). The reduction of cultured plates was 37.4% with the FUS200 and 58.3% with the UF-1000i. This study shows that both techniques improve the workflow in the laboratory, but the UF-1000i has the highest specificity at any sensitivity and the FUS200 needs a shorter processing time.